Existential Aspects of Positive Psychotherapy: Answers to the Challenges of Wartime - Svitlana Kyrychenko (The Global Psychotherapist, 2023)
The article presents the author’s perspective on various levels of psychological assistance that can be provided in crisis situations. The focus is primarily on the highest level of assistance, which is existential therapy. Within the context of existential therapy, the author emphasizes the importance of addressing existential aspects of positive psychotherapy.